Synthesis and characterisation of novel aluminium and gallium precursors for chemical vapour deposition1. (27th August 2015) - Knapp, Caroline E.; Marchand, Peter; Dyer, Caragh; Parkin, Ivan P.; Carmalt, Claire J.
<x xml:space="preserve">Abstract</x> Synthesis of novel β-ketoiminate compounds (aluminium and gallium) which have been used for the first time as precursors in (AACVD).